International Cultural Festivals and Local Economic Stimulation: Insights from a Heritage City in Indonesia (Universitas Terbuka, 2025)
This study examined how an international cultural festival stimulated local economic activity in a heritage city, using the Sawahlunto International Songket Silungkang Carnival (SISSCa) as a case study. The research addressed the limited understanding of how economic, social, and cultural impacts of festivals emerge and circulate beyond measurable expenditure outcomes. A qualitative case study approach was applied, with data collected through field observations, semi-structured interviews with key stakeholders, and analysis of official documents. Tourism System Theory was used to map actor interactions, while Multiplier Effect Theory guided the analysis of economic flows. The findings showed that SISSCa generated layered economic impacts through direct visitor spending, indirect supply-chain expansion, and induced household consumption. Policy interventions, including inclusive UMKM facilitation, cultural-based procurement, and free public access, played a critical role in amplifying these effects. In addition, the festival strengthened social cohesion, reinforced cultural identity, and enhanced Sawahlunto’s position as a heritage tourism destination. The study concluded that cultural festivals can function as sustainable instruments for local economic development when supported by coherent policy design and active community participation.